Dealing with Disaster and Environment in Indonesia Through Tradition and Quranic Understanding - Madjid Muh. Naim; Güler İsmail (E3S Web of Conferences)
Natural phenomena are inseparable aspect of human life. Some people give negative views on the natural occurrences and social phenomenon as the result of human act, but most of them strongly believe that these phenomenons are God’s test, the Lord of the ‘Alamin. In reality, they are anxious about their life, their families, their treasures, and their worldly affairs become destroyed when the natural disaster occurs. This study will discuss briefly on how people kindly understand, contemplate the qur’anic expressions about natural phenomenon, and do interaction deeply through the influential reading of Indonesia’s disasters by using technology. The scientific analysis and contemplation will be focused on the artistic depictions of holy Qur’an about disaster and environmental damage in Indonesia during last five years. This qualitative research uses a descriptive analytical approach to describe obviously the data which are obtained from the primary source (Qur’anic verses and Islamic scholar’s views) and the secondary source (questionnaire) by using simple random sampling (SRS).